2008
DOI: 10.1590/s0103-84782008000200023
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência bioeconômica da adubação de pastagem natural no sul do Brasil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
0
9
0
4
Order By: Relevance
“…efficiency of feed use (Almeida, 2005), mostly correlating a production input, such as hectare or kg of feed consumption, with kg of live weight produced. In the study of Santos et al (2008), for instance, the expression. "bioeconomic efficiency" was used to evaluate different nitrogen doses and their effects on gross profit per hectare and on benefit to cost ratio.…”
Section: Resultsmentioning
confidence: 99%
“…efficiency of feed use (Almeida, 2005), mostly correlating a production input, such as hectare or kg of feed consumption, with kg of live weight produced. In the study of Santos et al (2008), for instance, the expression. "bioeconomic efficiency" was used to evaluate different nitrogen doses and their effects on gross profit per hectare and on benefit to cost ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Para maximizar o uso das pastagens é necessário utilizar piqueteamento, respeitar a altura de pastejo, a lotação animal e o tempo de repouso (CORDOVA et al, 2012). A adubação recomendada por um profissional habilitado através da análise de solo permite a manutenção das pastagens perenes por tempo indeterminado e aumento da lotação animal (kg/peso vivo/área), e aumentar a quantidade de nutrientes das pastagens, que favorece a nutrição (SANTOS et al, 2008). É necessário instalar um sistema hídrico nos piquetes para os animais beberem água.…”
Section: Resultsunclassified
“…It should be noted that, to reach the profit an activity has generated, it first should return all the capital invested to its investors (farmer), that is, it shows the farmer how much worth or not worth investing and run business risks proposed (Antunes & Ries, 2001). Santos, Carvalho, Nabinger, Carassaii and Gomes (2008) evaluated the economic response of pasture fertilization consisting primarily of Paspalum notatum, with levels of 0, 100 and 200 kg N ha -1 , and found that the total cost was R$ 175.00, R$ 357.22 and R$ 539.44, the gross revenue was R$ 545.18, R$ 616.20 and R$ 1,045.20 and a gross margin of R$ 370.18, R$ 258.98 and R$ 505.76, respectively, and concluded that investment in pasture fertilization is economically feasible, regardless of the nitrogen level up to 200 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%